Physical features of soil quality under an agroforestry system - Carvalho, Rodrigo; Goedert, Wenceslau J.; Armando, Marcio Silveira (Pesquisa Agropecuaria Brasileira, 2004)
Agroforestry systems seem to be a sustainable alternative for agricultural production. The objective of this work was to evaluate the quality of a soil used under an agroforestry system by the quantification of the following soil physical attributes: density, porosity, resistance to penetration and aggregate stability. The soil under agroforestry exhibited a superior quality compared to the same soil cultivated by a conventional system, reflected by smaller soil density, higher porosity, lesser resistance to penetration and higher aggregate stability.
Keywords: soil density; porosity; compaction and aggregation; agroforestry